Hospital-based community cataract surgery: comparison of visual outcomes between conventional extra-capsular cataract extraction and small incision cataract surgery - Karki, P; Shrestha, JK; Shrestha, JB (Nepalese Journal of Ophthalmology, 2010)
Introduction: The small-incision cataract surgery is gaining popularity among the ophthalmic surgeons. Objective: To compare the visual outcome of conventional extra-capsular cataract extraction (ECCE) and small-incision cataract surgery (SICS) in a hospital based community cataract program. Materials and methods: A prospective interventional study without randomization was carried out including the patients undergoing cataract surgery by either conventional ECCE or manual SICS. They were followed up for 6 weeks postoperatively. The visual outcomes were compared between the two groups. Statistics: The statistical program Epi-Info version 2000 was used to analyze the data. Mean values with standard deviations, 95% CI and p value were calculated. The p value of <0.05 was considered significant. Results: Of 85 patients, 44 (M: F=10:34) underwent ECCE and 41 (M: F=15:26) SICS (RR= 0.71, 95% CI=0.42-1.2, p value=0.16). Unaided visual acuity on the 1st postoperative day in the ECCE group was e"6/ 18 in 22.7%,<6/18-6/60 in 63.6 %,< 6/60 in 13.7%, whereas in the SICS group, the same was e"6/18 in 70.7%,<6/18-6/60 in 22 %,< 6/60 in 7.3% (95% CI = 0.23 - 0.48, p=0.001). Best corrected visual acuity on the 6th week follow-up in the ECCE group was e"6/18 in 79.5%,<6/18-6/60 in 18.2 %,< 6/60 in 2.3% and in the SICS group the same was 6/18 in 90.5% and <6/18-6/60 in 4.9% (95% CI=0.44 - 0.73; p=0.0012). Conclusion: Both ECCE and SICS are good procedures for hospital based community cataract surgery but within the 6 weeks postoperative period SICS gives better visual outcome. Remarkably higher number of female patients can be provided service in a hospital based community cataract programme as compared to males. Keywords: cataract; small incision; extra-capsular DOI: 10.3126/nepjoph.v1i2.3686 Nep J Oph 2009;1(2):118-122